Surgery of ulcus cruris venosum - Schwahn-Schreiber, C. (Phlebologie, 2010)
Advanced chronic venous stasis syndrome is characterized by irreversible and self-perpetuating morphological alterations in the lower leg. A chronic inflammatory process results in sclerosis, which progresses from the skin to the subcutaneous tissue and ultimately the fascia, sometimes including muscle and ankle joint and leading to chronic compartment syndrome. To cure these severe alterations with non healing ulcers decompression of the compartments like paratibial fasciotomy with SEPS and crural fasciectomy or removal of sclerosis like shave therapy are successful surgical procedures. Indication should be adapted to the extension of ulcer. Indications of the operations and the techniques are described, complications and results are discussed. Due to ulcer extension especially shave therapy (removal of the sclerotic tissue epifascial) and crural fasciectomy (removal of sclerosis including fascia) are very successful with up to 80% healing rate, even in severe cases and even after long term (up to 8 years). Since shave therapy is easy, short and simple with short healing time, few complications and good aesthetical result it is the first choice of treatment for non healing leg ulcers. Fasci ectomy is reserved for special indications such as deep transfascial necrosis or failure of shave therapy.
Keywords: Ulcus cruris venosum; paratibial fascio tomy; fasci ectomy; shave therapy